A study about relationship between Research and Development (R&D) toward firm's financial performance selected international firms: panel data analysis / Yusma Nadhirah Mohd Yusof - Mohd Yusof, Yusma Nadhirah (2017)
Over the past few years, all researcher and scholar from all around the world shown a lot interest on research and development (R&D). It shown that R&D spending by most countries all over the world increase over the time. Economic boom on innovation and the application of a good way of latest know-how to add value of products and services and tactics of producing product and services especially by use research and development (R&D) investment. R&D investment is taken into consideration to be one of the most crucial elements for reinforcing technological development and economic growth for developed and developing countries. This research are conduct to investigate the impact of Research and Development (R&D) firm’s financial performance, Return on Asset (ROA) and Return on Equity (ROE). The findings, from both regression model shown that R&D show an impact toward firm’s financial performance are not significant and show negative relationship with ROA and ROE. While for other control variables, leverage ratio and number of employee shown significant relationship with ROA and ROE. Number of employee show negative relationship with ROA and ROE. But leverage ratio show negative when ROA dependent variable but positive relationship when ROE as the dependent variable.